Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1002/dev.20623
|View full text |Cite
|
Sign up to set email alerts
|

The development of stereotypic behavior in caged european starlings, Sturnus vulgaris

Abstract: Stereotypic behavior in captive animals has been hypothesized to emerge from thwarted natural behavior patterns and is thought to be more common in captive-reared animals. However, data on the early stages of developing stereotypies are currently scarce. We compared the development of stereotypic route-tracing and somersaulting in hand-reared and wild-caught starlings placed in individual cages for the first time. We found that wild-caught birds were less active but showed more escape motivation and more evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 31 publications
2
18
1
Order By: Relevance
“…Other sequences that were less or not described or recognized were simply considered as abnormal repetitive behaviours (ARBs). Most of these behaviours have been already described by other authors [19], [20], [22]. We describe below the only SB and the 5 ARBs that we observed.…”
Section: Methodssupporting
confidence: 78%
See 2 more Smart Citations
“…Other sequences that were less or not described or recognized were simply considered as abnormal repetitive behaviours (ARBs). Most of these behaviours have been already described by other authors [19], [20], [22]. We describe below the only SB and the 5 ARBs that we observed.…”
Section: Methodssupporting
confidence: 78%
“…Although five days may appear as a rather short period of time, it has been shown that starlings can exhibit SBs within a week of being placed in a cage [20]. Moreover, this time span was sufficient for us to observe significant effects of the video presentations compared to the controls and significant changes between the first and the last days of the experiment (see results).…”
Section: Methodsmentioning
confidence: 71%
See 1 more Smart Citation
“…As stated by Magnusson (2000, p. 94), "that is, if A is an earlier and B a later component of the same recurring temporal pattern then after an occurrence of A at t, there is an interval [t+d1, t +d2] (d2≥d1≥d0) that tends to contain at least one occurrence of B more often than would be expected by chance". This software has been extensively used in several areas of knowledge both in animal (Feenders & Bateson, 2012;Nicol, Segonds-Pichon, & Magnusson, 2015) and human studies (Sandman, Kemp, Mabini, Pincus, & Magnusson, 2012;Woods, Yefimova, & Brecht, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The number of different T-patterns and the total number of T-patterns detected have been used as measures of route-tracing behavior. Results demonstrated that wild-caught starlings showed higher numbers of T-patterns indicating more route-tracing (Feenders and Bateson, 2012). Interestingly, some evidence showed that hand-reared starlings were noticeably less neophobic and less impulsive than wild-caught ones (Feenders and Bateson, 2013).…”
Section: T-patterns In Animal Behaviormentioning
confidence: 97%